2008
DOI: 10.1523/jneurosci.3733-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Generation of Two Distinct Synapse-Driven Network Patterns in Developing Neocortex

Abstract: Developing cortical networks generate a variety of coherent activity patterns that participate in circuit refinement. Early network oscillations (ENOs) are the dominant network pattern in the rodent neocortex for a short period after birth. These large-scale calcium waves were shown to be largely driven by glutamatergic synapses albeit GABA is a major excitatory neurotransmitter in the cortex at such early stages, mediating synapse-driven giant depolarizing potentials (GDPs) in the hippocampus. Using functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
281
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(310 citation statements)
references
References 65 publications
(114 reference statements)
16
281
2
Order By: Relevance
“…These data suggest that the network oscillations in the superficial neocortical layers of mice during P5-6 are mainly cGDPs (24). cGDPs appear to be strongly dependent on the actions of GABA as they are almost completely blocked by the GABA A receptor antagonist (24). Our study indicates that, besides GABAergic transmission, CX26-mediated electrical coupling between excitatory neurons contributes to the expression of cGDPs at early postnatal stages.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…These data suggest that the network oscillations in the superficial neocortical layers of mice during P5-6 are mainly cGDPs (24). cGDPs appear to be strongly dependent on the actions of GABA as they are almost completely blocked by the GABA A receptor antagonist (24). Our study indicates that, besides GABAergic transmission, CX26-mediated electrical coupling between excitatory neurons contributes to the expression of cGDPs at early postnatal stages.…”
Section: Discussionmentioning
confidence: 53%
“…We found that the network oscillations in the superficial neocortical layers of mice during P5-6 display two features: (i) the frequency is ∼0.1 Hz, and (ii) the synchronicity duration is less than 200 ms. These data suggest that the network oscillations in the superficial neocortical layers of mice during P5-6 are mainly cGDPs (24). cGDPs appear to be strongly dependent on the actions of GABA as they are almost completely blocked by the GABA A receptor antagonist (24).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Endogenous rhythmic activity is a key feature of immature neural networks that has been described in many developing structures of the CNS, including the retina, cochlea, spinal cord, hindbrain, cerebellum, thalamus, hippocampus, and cortex (Galli and Maffei, 1988;Ben-Ari et al, 1989;Yuste et al, 1992;O'Donovan, 1999;Garaschuk et al, 2000;Ben-Ari, 2002;Leinekugel et al, 2002;Yvert et al, 2004;Hunt et al, 2005;Dupont et al, 2006;Spitzer, 2006;Momose-Sato et al, 2007;Allène et al, 2008;Blankenship and Feller, 2010), and shown to be essential for the establishment of functional network connectivity (Penn et al, 1998;Hanson and Landmesser, 2004;Cang et al, 2005). Although previous studies have been devoted to deciphering the cellular and synaptic mechanisms underlying such activity (Tabak et al, 2000;Ben-Ari, 2002), the primal mechanism responsible for the generation of immature rhythms remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%